Comprehensive Seismic Analysis and Design Strategies for Enhanced Building Resilience: A Comparative Study of Regular and Irregular Structures - Dhritiman Talukdar; Mrinal Kanti Sen
Seismic analysis assesses how buildings or infrastructure respond to forces induced by earthquakes, examining the impact of ground motion and evaluating the structure$1 (Bs ability to endure and mitigate potential seismic damage. Structures incorporate elements such as shear walls, bracing structures, dampers, and base isolation systems to resist lateral loads from earthquakes. These elements contribute to enhancing the seismic performance of the structure. This research compares diverse seismic parameters across six building models, including storey displacement and drift, base shear, and time period of vibration. Model 1 represents a simple regular building without having any elements, while Model 2 incorporates shear walls, bracings, and dampers, Model 3 utilises base isolation, Model 4 adopts an L-shaped irregular building, Model 5 assumes a C-shaped irregular building, and Model 6 represents an I-shaped irregular building. The plan area of the model cases remains constant. Following the design of the models, seismic analyses are conducted, encompassing linear and non-linear as well as static and dynamic analysis. The models undergo design and seismic analysis utilising SAP2000 software, adhering to Indian Standard codes under various loading conditions.s